Multilayer film and manufacturing method thereof

The method of forming a heat-melt tetrafluoroethylene polymer layer on a polyimide film within a controlled temperature range addresses the challenges of adhesion and drilling processability in multilayer films, resulting in a film with improved properties for high-frequency signal transmission.

JP7647738B2Active Publication Date: 2025-03-18AGC INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2022501920
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-19
Filing Date
2021-02-17
Publication Date
2025-03-18
Estimated Expiration
2041-02-17

AI Technical Summary

Technical Problem

Existing multilayer films used in printed wiring boards face challenges in achieving excellent adhesion between layers and drilling processability while minimizing wrinkles.

Method used

A method involving the formation of a layer containing a heat-melt tetrafluoroethylene polymer on a polyimide film with a specific glass transition point, using a liquid composition with tetrafluoroethylene polymer powder and optionally a pyrolytic polymer, and heating within a controlled temperature range to enhance adhesion and prevent wrinkles.

Benefits of technology

The method results in a multilayer film with improved adhesion and drilling properties, minimal wrinkles, and enhanced peel strength, making it suitable for high-frequency signal transmission applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647738000001
    Figure 0007647738000001
  • Figure 0007647738000002
    Figure 0007647738000002
  • Figure 0007647738000003
    Figure 0007647738000003
Patent Text Reader

Abstract

[Problem] To provide a method for manufacturing a multilayer film having excellent adhesion and drilling workability and having no wrinkles or extremely few wrinkles, to provide said multilayer film, and also to provide a method for manufacturing a multilayer film with improved interlayer adhesion, and to provide said multilayer film. [Solution] This method for manufacturing a multilayer film includes: disposing a liquid composition containing powder of a thermally fusible tetrafluoroethylene polymer on the surface of a layer containing polyimide having a glass transition point; and applying heat at a temperature that is higher than the melting point of the tetrafluoroethylene polymer and that is at the polyimide glass transition point+40°C or lower, thereby forming a layer containing the tetrafluoroethylene polymer. Another method for manufacturing a multilayer film includes: disposing a liquid composition containing powder of a thermally fusible tetrafluoroethylene polymer and a thermally degradable polymer on the surface of a polyimide film layer; and applying heat to form a layer containing the tetrafluoroethylene polymer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multilayer film having a layer containing a polyimide and a layer containing a tetrafluoroethylene-based polymer, and a method for producing the same. [Background technology]

[0002] A printed wiring board used for transmitting high frequency signals is required to have excellent transmission characteristics. To improve the transmission characteristics, it is necessary to use a material with a low relative dielectric constant and dielectric loss tangent for the insulating layer of the printed wiring board. As such a material, a multilayer film having a layer containing polyimide and a layer containing a tetrafluoroethylene-based polymer is known. When this multilayer film is used as an insulating layer for a printed wiring board, excellent drilling workability is required in order to form via holes.

[0003] Patent Document 1 describes a method for producing the multilayer film by laminating a film containing polyimide and a film containing a tetrafluoroethylene polymer. Furthermore, Patent Documents 2 to 4 propose a method for forming a layer containing a tetrafluoroethylene-based polymer in the above multilayer film by applying a dispersion containing tetrafluoroethylene-based polymer powder to a polyimide film and heating it. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2010 / 084867 [Patent Document 2] Japanese Patent Application Publication No. 09-157418 [Patent Document 3] JP 2000-211081 A [Patent Document 4] JP 2005-035300 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present inventors have investigated a method for producing a multilayer film that has excellent adhesion between adjacent layers, excellent hole-punching processability, and that generates few or no wrinkles, with the aim of expanding the scope of use of the multilayer film. According to the study by the present inventors, when the multilayer film is produced by laminating films, a film having satisfactory hole-forming processability cannot be produced. On the other hand, when the multilayer film is produced from a dispersion, the polyimide film shrinks during baking of the tetrafluoroethylene-based polymer, and wrinkles occur in the multilayer film.

[0006] An object of the present invention is to provide a method for producing a multilayer film which has excellent adhesion and drilling processability and which generates no or very few wrinkles, and a multilayer film. In recent years, there has been a demand for further improvement in the adhesion between layers of the multilayer film. An object of the present invention is to provide a multilayer film having a polyimide film as a base layer and a tetrafluoroethylene polymer layer provided on the surface of the base layer, the multilayer film having excellent interlayer adhesion, and a method for producing the multilayer film. [Means for solving the problem]

[0007] The present inventors have conducted extensive research and found that in order to obtain a multilayer film that has excellent adhesion and drilling processability and generates no or very few wrinkles, it is necessary to use a polyimide having a glass transition point and a heat-fusible tetrafluoroethylene-based polymer, and to form a layer containing the heat-fusible tetrafluoroethylene-based polymer in a specified temperature range. Furthermore, the present inventors have conducted extensive research and found that in order to obtain a multilayer film having excellent interlayer adhesion, it is necessary to form a layer containing a specified tetrafluoroethylene-based polymer powder and a thermally decomposable polymer on the surface of a polyimide film layer. The present invention has the following aspects. (1) A method for producing a multilayer film, comprising: placing a liquid composition containing a powder of a heat-fusible tetrafluoroethylene-based polymer on the surface of a layer containing a polyimide having a glass transition point; heating the liquid composition at a temperature higher than the melting point of the tetrafluoroethylene-based polymer and not higher than the glass transition point of the polyimide + 40°C to form a layer containing the tetrafluoroethylene-based polymer; and obtaining a multilayer film having a layer containing the polyimide and a layer containing the tetrafluoroethylene-based polymer formed on the surface of the layer containing the polyimide. (2) The method according to (1), wherein the tetrafluoroethylene polymer is a tetrafluoroethylene polymer containing units based on perfluoro(alkyl vinyl ether). (3) The method for producing the tetrafluoroethylene-based polymer according to (1) or (2), wherein the tetrafluoroethylene-based polymer is a polymer having a polar functional group, or a polymer containing 2.0 to 5.0 mol % of a unit based on perfluoro(alkyl vinyl ether) relative to all units and not having a polar functional group. (4) The method according to any one of (1) to (3), wherein the liquid composition further contains an aromatic polymer. (5) The method according to any one of (1) to (4), wherein the layer containing the tetrafluoroethylene polymer has a thickness of 100 μm or less. (6) The method according to any one of (1) to (5), wherein the ratio of the thickness of the layer containing the tetrafluoroethylene polymer to the thickness of the layer containing the polyimide is 0.4 or more. (7) The method according to any one of (1) to (6), wherein a layer containing the tetrafluoroethylene polymer is formed on each of both sides of the layer containing the polyimide. (8) A multilayer film comprising a layer containing a polyimide having a glass transition point and layers containing a heat-fusible tetrafluoroethylene-based polymer formed on both sides of the polyimide-containing layer, the glass transition point of the polyimide being higher than the melting point of the tetrafluoroethylene-based polymer and not higher than the melting point of the tetrafluoroethylene-based polymer + 60°C. (9) The multilayer film according to (8), wherein the tetrafluoroethylene-based polymer is a tetrafluoroethylene-based polymer containing units based on perfluoro(alkyl vinyl ether). (10) The multilayer film according to (8) or (9), wherein the tetrafluoroethylene-based polymer is a polymer having a polar functional group, or a polymer containing 2.0 to 5.0 mol % of units based on perfluoro(alkyl vinyl ether) relative to all units and having no polar functional group. (11) The multilayer film according to any one of (8) to (10), wherein the tetrafluoroethylene polymer has a melting point of 260 to 325°C. (12) The multilayer film according to any one of (8) to (11), wherein the polyimide has a glass transition point of 300 to 380° C. (13) The multilayer film according to any one of (8) to (12), wherein the water absorption rate of the film is 0.3% or less. (14) The multilayer film according to any one of (8) to (13), wherein the peel strength of the film is 10 N / cm or more. (15) A method for producing a multilayer film, comprising: placing a liquid composition containing a powder of a heat-fusible tetrafluoroethylene-based polymer and a thermally decomposable polymer on a surface of a polyimide film layer; heating the mixture to form a layer containing the tetrafluoroethylene-based polymer; and obtaining a multilayer film having the polyimide film layer and a layer containing a tetrafluoroethylene-based polymer formed on the surface of the polyimide film layer. (16) The method according to (15), wherein the thermally decomposable polymer is a (meth)acrylic polymer. (17) The method according to (15) or (16), wherein the tetrafluoroethylene polymer is a tetrafluoroethylene polymer containing a unit based on perfluoro(alkyl vinyl ether). (18) The process according to any one of (15) to (17), wherein the tetrafluoroethylene polymer is a polymer having a polar functional group, or a polymer containing 2.0 to 5.0 mol % of units based on perfluoro(alkyl vinyl ether) relative to all units and having no polar functional group. (19) The method according to any one of (15) to (18), wherein the thermally decomposable polymer is a (meth)acrylic polymer having any one of groups represented by the following formulae (1) to (5) in a side chain: Formula (1)-C(O)-OC(-R 11 )(-R 12 )(-R 13 ) Formula (2) -C(O)-OCH(-R 21 )(-OR 22 ) Formula (3)-C(O)-OQ 3 -O-CF(CF3)(-R 31 ) Formula (4)-C(O)-OQ 4 -OC(CF3)(=C(-R 41 )(-R 42 )) Formula (5)-C(O)-OC(CF3)2(-R 51 ) The symbols in the formula have the following meanings. R 11 , R 12 and R 13 is R 11 , R 12 and R 13 are each independently an alkyl group or an aryl group, or R 11 and R 12 is a hydrogen atom and R 13 is an aryl group or R 11 and R 12 are each independently a hydrogen atom or an alkyl group, and R 13 is an alkoxy group or R 11 is a hydrogen atom or an alkyl group, and R 12 and R 13 are groups which together form an alkylene group. R 21 and R 22 is R 21 is an alkyl group and R 22 is a fluoroalkyl group or is a group which together forms an alkylene group. Q 3 and Q 4 are each independently an alkylene group. R31 is a perfluoroalkenyl group. R 41 and R 42 are each independently a perfluoroalkyl group. R 51 is an alkyl group or a cycloalkyl group. (20) The method according to any one of (15) to (19), wherein the polyimide in the polyimide film layer is a polyimide having an imide group density of 0.35 or less. (21) The method according to any one of (15) to (20), wherein the polyimide of the polyimide film layer is a polyimide containing a unit based on an aromatic diamine or an aliphatic diamine having a structure in which two or more arylene groups are linked via a linking group. (22) The method according to any one of (15) to (21), wherein the polyimide of the polyimide film layer contains a unit based on an acid dianhydride of an aromatic tetracarboxylic acid, and the acid dianhydride of the aromatic tetracarboxylic acid has a structure in which two phthalic anhydride structures are linked via a linking group. (23) The method according to any one of (15) to (22), wherein the liquid composition contains a polyimide or a polyimide precursor. (24) A multilayer film having a polyimide film layer and, on both sides of the polyimide film layer, layers containing a heat-fusible tetrafluoroethylene polymer and a heat-decomposable polymer. (25) The multilayer film according to (24), wherein the polyimide in the polyimide film layer is a polyimide having an imide group density of 0.35 or less. (26) The multilayer film according to (24) or (25), wherein the tetrafluoroethylene-based polymer is a tetrafluoroethylene-based polymer containing units based on perfluoro(alkyl vinyl ether). (27) The multilayer film according to any one of (24) to (26), wherein the tetrafluoroethylene-based polymer is a polymer having a polar functional group, or a polymer containing 2.0 to 5.0 mol % of units based on perfluoro(alkyl vinyl ether) relative to all units and having no polar functional group. (28) The multilayer film according to any one of (24) to (27), wherein the layer further contains an aromatic polymer. (29) The multilayer film according to any one of (24) to (28), wherein the layer contains a thermal decomposition product derived from the thermally decomposable polymer. Effect of the Invention

[0008] According to the present invention, a method for producing a multilayer film which has excellent adhesion and drilling processability and which generates no or very few wrinkles, and a multilayer film can be obtained. Furthermore, according to the present invention, a method for producing a multilayer film having excellent interlayer adhesion and a multilayer film can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The following terms have the following meanings. The phrase "having a glass transition point (hereinafter also referred to as "Tg")" means that the Tg is measurable when the polymer is analyzed by a solid dynamic viscoelasticity (hereinafter also referred to as "DMA") method. "Tg of a polymer" is a value measured by analyzing a polymer by the DMA method. The "tetrafluoroethylene-based polymer" is a polymer containing units based on tetrafluoroethylene (hereinafter also referred to as "TFE units"), and is also simply referred to as a "TFE-based polymer". The term "thermally meltable tetrafluoroethylene polymer" refers to a polymer that melts without hardening when measured by differential scanning calorimetry (hereinafter also referred to as "DSC") method. The "melting temperature (melting point) of a polymer" is the temperature corresponding to the maximum value of the melting peak of the polymer as measured by differential scanning calorimetry (DSC).

[0010] "Polyimide imide group density" refers to the value obtained by dividing the molecular weight of the imide group portion (140.1) by the molecular weight per unit. For example, in the case of a polyimide obtained by imidizing a polyimide precursor consisting of two components, 1 mol of pyromellitic dianhydride and 1 mol of 3,4'-oxydianiline, the molecular weight per unit is 382.4, and the imide group density is 0.37 (140.1 / 382.4).

[0011] The "water absorption rate" refers to the rate of mass change (%) of the test specimen before and after immersion [{(mass after immersion in water - mass before immersion in water) / mass before immersion} x 100], where the mass of the test specimen at the time of cooling in a desiccator is defined as the mass of the test specimen before immersion in water, and then the dried test specimen is immersed in pure water at 23°C for 24 hours. The test specimen is then removed from the pure water and the moisture on the surface is quickly wiped off. The mass of the test specimen after immersion in water is then measured within 1 minute, and this is defined as the mass of the test specimen before and after immersion.

[0012] The term "peel strength" refers to the maximum load measured when a rectangular test piece 100 mm long and 10 mm wide is cut out, a PI layer and a TFE-based polymer layer are peeled off from one end of the test piece in the longitudinal direction to a position 50 mm from the end, and then the test piece is peeled off at a 90° angle at a tensile speed of 50 mm / min using a tensile tester, with the position 50 mm from the end of the test piece in the longitudinal direction as the center.

[0013] "Yield strength" refers to the stress at which, as the strain is increased, the relationship between the strain and the stress becomes no longer proportional, and the phenomenon begins to occur in which the strain remains even after the stress is removed. It is defined as the "stress at 5% strain" value when the tensile modulus of the base film is measured in accordance with ASTM D882. "Low plastic deformation resistance" refers to the property that the stress increases when the base film is plastically deformed, or the property that a large stress is required when the base film is plastically deformed, and is defined as the value of "stress at 15% strain" when the tensile modulus of the base film is measured according to ASTM D882.

[0014] "Powder D50" is the particle diameter (volume-based cumulative 50% diameter) at the point on the cumulative curve where the cumulative volume is 50% when the particle size distribution of the powder is measured by laser diffraction / scattering and the total volume of the group of particles that make up the powder is set to 100%. "D90 of powder" is the volume-based cumulative 90% diameter of the powder measured in a similar manner. The values ​​of D50 and D90 were measured by dispersing the powder in water using a laser diffraction / scattering particle size distribution analyzer (LA-920, manufactured by Horiba, Ltd.).

[0015] The "viscosity of the liquid composition" is a value measured for the liquid composition using a Brookfield viscometer at room temperature (25°C) and a rotation speed of 30 rpm. The measurement is repeated three times, and the average value of the three measured values ​​is used.

[0016] The "unit" in a polymer may be an atomic group formed directly from a monomer by a polymerization reaction, or may be an atomic group in which a part of the structure is converted by treating a polymer obtained by a polymerization reaction in a predetermined manner. A unit based on monomer A is also referred to as a monomer A unit. "Ten-point average roughness (Rzjis) of the surface of metal foil" is a value specified in Appendix JA of JIS B 0601:2013.

[0017] The manufacturing method of the present invention (hereinafter also referred to as "this method") is a method in which a liquid composition containing a powder of a heat-fusible tetrafluoroethylene-based polymer (hereinafter also referred to as "TFE-based polymer") is placed on the surface of a layer containing polyimide (hereinafter also referred to as "PI") (hereinafter also referred to as "PI layer"), and heated to form a layer containing the TFE-based polymer, thereby obtaining a multilayer film having the PI layer and a layer containing a TFE-based polymer (hereinafter also referred to as "TFE-based polymer layer") formed on the surface of the PI layer.

[0018] The first manufacturing method of the present invention (hereinafter also referred to as "Method 1") is a method in which a liquid composition containing a TFE-based polymer powder is placed on the surface of a PI layer (hereinafter also referred to as "PI layer 1") containing a PI having a Tg (hereinafter also referred to as "PI1"), and heated at a temperature above the melting point of the TFE-based polymer and not higher than Tg+40°C of PI1 to form a layer containing a TFE-based polymer (hereinafter also referred to as "TFE-based polymer layer 1"), thereby obtaining a multilayer film having the PI layer 1 and the TFE-based polymer layer 1 formed on the surface of the PI layer 1.

[0019] According to method 1, a multilayer film having excellent adhesion and drilling processability and having no or very few wrinkles can be obtained. The reason for this is not entirely clear, but is thought to be as follows. The shrinkage of the PI layer 1 caused by heating promotes densification of the PI layer 1 and improves physical properties such as water resistance, but it also causes wrinkles and reduces adhesion between the layers and the drilling processability of the multilayer film. In other words, it has been difficult to manufacture a dense multilayer film that has these physical properties while controlling the shrinkage.

[0020] Therefore, in method 1, a thermally meltable TFE-based polymer and a PI having a Tg are used, and heating is performed at a temperature above the melting point of the TFE-based polymer and below Tg+40°C of the PI. In other words, during heating, the PI layer 1 is softened while the TFE-based polymer powder is melted to form the TFE-based polymer layer 1. It is believed that this promotes high adhesion between the TFE-based polymer layer 1 and the PI layer 1, and controls shrinkage. It is believed that due to this mechanism of action, method 1 can produce a dense multilayer film that has excellent adhesion and drilling processability and has no or very few wrinkles.

[0021] In Method 1, the Tg of PI1 is preferably 300° C. or higher, and more preferably 310° C. or higher. The Tg of PI1 is preferably 380° C. or lower, and more preferably 360° C. or lower. In this case, not only is it easier for the softening of the PI layer 1 and the melting of the powder to proceed in a more balanced manner upon heating, but the PI layer 1 and the TFE-based polymer layer 1 also adhere to each other more closely, which makes it easier for the physical properties (high peel strength, water resistance, low linear expansion, etc.) of the resulting multilayer film to be improved.

[0022] PI1 is preferably an aromatic polyimide. Examples of aromatic polyimides include polyimides obtained by reacting a diamine with a carboxylic dianhydride to synthesize a polyamic acid, and then imidizing the polyamic acid by a thermal imidization method or a chemical imidization method.

[0023] The diamine is preferably an aromatic diamine. Specific examples of the aromatic diamine include 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenylmethane, 4,4'-oxydianiline, 3,3'-oxydianiline, 3,4'-oxydianiline, 4,4'-diaminodiphenyldiethylsilane, 4,4'-diaminodiphenylsilane, 1,4-diaminobenzene (p-phenylenediamine), 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 1,3-bis(3-aminophenoxy)biphenyl, and 1,3-bis(3-aminophenoxy)biphenyl. Examples of the diamine include 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2-bis{4-(4-aminophenoxy)phenyl}propane, 3,3'-dihydroxy-4,4'-diamino-1,1'-biphenyl, and 2,4-diaminotoluene. The diamine may be used alone or in combination of two or more.

[0024] Examples of carboxylic acid dianhydrides include pyromellitic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 2,2',3,3'-biphenyl tetracarboxylic dianhydride, 2,3,3',4'-biphenyl tetracarboxylic dianhydride, 3,3',4,4'-biphenyl ether tetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3 ,4-dicarboxyphenyl)methane dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2,3,2',3'-benzophenone tetracarboxylic dianhydride, 2,3,3',4'-benzophenone tetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxyphenyl)-1,1,3,3-tetramethyldicyclohexane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]hexafluoropropane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride. The carboxylic dianhydride may be used alone or in combination of two or more.

[0025] The ratio of the total number of moles of oxygen atoms derived from ether bonds contained in the diamine and the carboxylic dianhydride to the total number of moles of the diamine and the carboxylic dianhydride is preferably 35 to 70%, more preferably 45 to 65%. In this case, the flexibility of the polymer main chain of PI1 is increased, and the stacking property of the aromatic rings is improved, thereby further improving the adhesion between the PI layer 1 and the TFE-based polymer layer 1. In this case, the punching processability of the multilayer film of the present invention is also improved.

[0026] The imide group density of PI1 is preferably 0.4 or less, more preferably 0.3 or less, and more preferably 0.1 or more. In this case, the softening of the PI layer 1 and the melting of the powder during heating are more balanced and tend to proceed more easily.

[0027] The PI layer 1 in the present method 1 may contain an inorganic filler for the purpose of improving properties such as yield strength, plastic deformation resistance, thermal conductivity, loop stiffness, etc. Examples of such inorganic fillers include silicon oxide, titanium oxide, aluminum oxide, silicon nitride, boron nitride, calcium hydrogen phosphate, and calcium phosphate.

[0028] The tensile modulus of the PI layer 1 is preferably 5 GPa or more, more preferably 10 GPa or more. The tensile modulus is preferably 25 GPa or less, more preferably 20 GPa or less. By using a PI layer 1 having a tensile modulus in this range, the above-mentioned mechanism of action of the present method 1 is improved, and the occurrence of wrinkles in the obtained multilayer film can be more reliably prevented. As a result, a multilayer film with high surface smoothness can be obtained.

[0029] The stress at 5% strain of the PI layer 1 is preferably 180 MPa or more, more preferably 210 MPa or more, and is preferably 500 MPa or less. The stress of the PI layer 1 at 15% strain is preferably 225 MPa or more, more preferably 245 MPa or more, and is preferably 580 MPa or less. Such a PI layer 1 has high yield strength and is resistant to plastic deformation, and can reduce the linear expansion coefficient of the resulting multilayer film and more reliably prevent wrinkles from occurring therein.

[0030] The TFE-based polymer in this method preferably further contains units (PAVE units) based on perfluoro(alkyl vinyl ether) (PAVE), which facilitates a more balanced process of softening the PI layer 1 and melting the powder during heating.

[0031] The melting point of the TFE-based polymer is preferably 260 to 325° C., and more preferably 280 to 320° C. In this case, not only the softening of the PI layer 1 and the melting of the powder during heating proceed in a more balanced manner, but also the PI layer 1 and the TFE-based polymer layer 1 are more closely attached to each other, which tends to improve the physical properties of the resulting multilayer film. The Tg of the TFE polymer is preferably from 75 to 125°C, more preferably from 80 to 100°C.

[0032] The TFE-based polymer preferably has a polar functional group. The polar functional group may be contained in a unit in the TFE-based polymer, or may be contained in a terminal group of the main chain of the polymer. Examples of the latter embodiment include a TFE-based polymer having a polar functional group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and a TFE-based polymer having a polar functional group obtained by subjecting a TFE-based polymer to plasma treatment or ionizing radiation treatment.

[0033] The polar functional group is preferably a hydroxyl group-containing group or a carbonyl group-containing group, and from the viewpoint of enhancing the state stability of the liquid composition, a carbonyl group-containing group is particularly preferable. The hydroxyl-containing group is preferably a group containing an alcoholic hydroxyl group, and is preferably -CF2CH2OH or -C(CF3)2OH. The carbonyl group-containing group is a group containing a carbonyl group (>C(O)), and is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.) or a carbonate group (-OC(O)O-). When the TFE-based polymer has a carbonyl group-containing group, the number of the carbonyl group-containing groups in the TFE-based polymer is 1×10 6The number of carbonyl-containing groups per unit is preferably 10 to 5000, more preferably 50 to 4000, and even more preferably 100 to 2000. In this case, the TFE-based polymer is likely to interact with the PI layer 1, and the peel strength of the resulting multilayer film is likely to be improved. In addition, the linear expansion coefficient of the resulting multilayer film can be reduced, and the occurrence of wrinkles in the film can be more reliably prevented. The number of carbonyl-containing groups in the TFE-based polymer can be quantified by the composition of the polymer or the method described in International Publication WO2020 / 145133.

[0034] The TFE-based polymer has a melting point of 260 to 320°C and is preferably a polymer containing PAVE units, with the PAVE units accounting for 1.0 to 5.0 mol% of the total units. More preferred is a TFE-based polymer (1) containing TFE units and PAVE units, with the PAVE units accounting for 1.0 to 5.0 mol% of the total units, and having a polar functional group, or a TFE-based polymer (2) containing TFE units and PAVE units, with the PAVE units accounting for 2.0 to 5.0 mol% of the total units, and having no polar functional group. From the viewpoints of adhesion and water resistance, the TFE-based polymer (1) is particularly preferred. The TFE polymer (1) preferably contains a TFE unit, a PAVE unit, and a unit based on a monomer having a polar functional group. The TFE polymer (1) or (2) not only has excellent dispersibility in liquid as a powder, but also easily forms fine spherulites during the formation of the TFE polymer layer 1, and thus tends to further improve the adhesion with the PI layer 1.

[0035] The TFE polymer (1) preferably contains, based on all units, 94 to 98.99 mol % of TFE units, 1.0 to 5.0 mol % of PAVE units, and 0.01 to 3.0 mol % of units based on a monomer having a polar functional group. Moreover, the monomer having a polar functional group is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic anhydride (also called himic anhydride; hereinafter, also referred to as "NAH"). Specific examples of the TFE-based polymer (1) include the polymers described in WO 2018 / 16644.

[0036] The TFE polymer (2) is composed only of TFE units and PAVE units, and preferably contains 95.0 to 98.0 mol % of TFE units and 2.0 to 5.0 mol % of PAVE units based on all units. The content of the PAVE unit in the TFE polymer (2) is preferably 2.1 mol % or more, more preferably 2.2 mol % or more, based on all units. In addition, the TFE-based polymer (2) having no polar functional group is defined as having a polar functional group less than 1×10 of the number of carbon atoms constituting the polymer main chain. 6 This means that the number of polar functional groups per unit of the polymer is less than 500. The number of the polar functional groups is preferably 100 or less, and particularly preferably less than 50. The lower limit of the number of the polar functional groups is usually 0. The TFE-based polymer (2) may be produced using a polymerization initiator or a chain transfer agent that does not generate a polar functional group as a terminal group of the polymer chain, or may be produced by fluorinating an F polymer having a polar functional group (such as an F polymer having a polar functional group derived from a polymerization initiator at the terminal group of the main chain of the polymer). As a method for fluorination, a method using fluorine gas (see JP 2019-194314 A, etc.) can be mentioned.

[0037] The content of the TFE-based polymer in the TFE-based polymer powder is preferably 80% by mass or more, and more preferably 100% by mass. The D50 of the powder is preferably 10 μm or less, more preferably 6 μm or less, and even more preferably 4 μm or less. The D50 of the powder is preferably 0.01 μm or more, more preferably 0.1 μm or more, and even more preferably 1 μm or more. The D90 of the powder is preferably 10 μm or less.

[0038] The powder of the TFE-based polymer may contain inorganic substances or polymers different from the TFE-based polymer. Examples of inorganic substances include, preferably, oxides, nitrides, simple metals, alloys, and carbon, more preferably, metal oxides such as silicon oxide (silica), beryllium oxide, cerium oxide, alumina, soda alumina, magnesium oxide, zinc oxide, and titanium oxide, boron nitride, stearinite, and magnesium metasilicate, further preferably, silica and boron nitride, and particularly preferably, silica. Examples of different polymers include aromatic polymers, such as aromatic elastomers, such as styrene elastomers, aromatic polyimides, aromatic maleimides, and aromatic polyamic acids. The powder of the TFE-based polymer containing an inorganic substance or a different polymer preferably has a core-shell structure having a TFE-based polymer as the core and the above-mentioned component as the shell, or has a core-shell structure having a TFE-based polymer as the shell and the above-mentioned component as the core. The powder having such a core-shell structure is obtained, for example, by causing particles of the TFE-based polymer and particles of the above-mentioned component to coalesce by collision or aggregation.

[0039] The liquid composition in Method 1 is a dispersion in which a TFE-based polymer powder is dispersed. The liquid composition preferably comprises a liquid dispersion medium. The liquid dispersion medium is a dispersion medium for the above powder that is liquid at 25° C. The liquid dispersion medium may be used alone or in combination of two or more kinds. The boiling point of the liquid dispersion medium is preferably 125 to 250° C. Within this range, when the liquid dispersion medium is evaporated from the liquid composition, the powder is highly fluidized and densely packed, and as a result, a dense TFE-based polymer layer is easily formed. The liquid dispersion medium is preferably an aprotic polar medium.

[0040] Specific examples of liquid dispersion media include water, 1-propanol, 2-propanol, 1-butanol, 1-methoxy-2-propanol, N,N-dimethylformamide, N,N-dimethylacetamide, methyl ethyl ketone, N-methyl-2-pyrrolidone (hereinafter also referred to as "NMP"), γ-butyrolactone, cyclohexanone, cyclopentanone, dimethyl sulfoxide, diethyl ether, dioxane, butyl acetate, methyl isopropyl ketone, cyclopentanone, cyclohexanone, ethylene glycol monoisopropyl ether, and cellosolve (methyl cellosolve, ethyl cellosolve, etc.). From the viewpoints of adjusting the liquid properties (viscosity, thixotropy ratio, etc.) of the liquid composition and achieving a high level of interaction between the components, the liquid dispersion medium is preferably an ester, a ketone, or an amide, and more preferably γ-butyrolactone, methyl ethyl ketone, cyclohexanone, N,N-dimethylformamide, or NMP.

[0041] The content of the TFE polymer in the liquid composition is preferably 10% by mass or more, more preferably 25% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less.

[0042] The liquid composition preferably further contains an aromatic polymer (hereinafter also referred to as "AR polymer"). In this case, the occurrence of warping and peeling of the TFE-based polymer layer 1 is sufficiently suppressed, and the adhesion of the resulting multilayer film to other substrates is also improved. This is considered to be due to the fact that the AR-based polymer is highly dispersed in the TFE-based polymer layer 1, not only mitigating the linear expansion of the TFE-based polymer layer 1, but also causing an interaction with the PI layer 1 due to the aromatic ring of the AR-based polymer present in the surface layer of the TFE-based polymer layer 1. Specifically, it is considered that the aromatic ring of the AR-based polymer and the aromatic ring of the PI 1 present near the interface between the TFE-based polymer layer 1 and the PI layer 1 are stacked, thereby improving the adhesion of the TFE-based polymer layer 1 to the PI layer 1.

[0043] The AR polymer is preferably an aromatic polyimide or an aromatic bismaleimide, which not only tends to improve the adhesion of the TFE polymer layer 1 to the PI layer 1 but also tends to improve the physical properties (UV absorbency, etc.) of the multilayer film. The 5% mass loss temperature of the AR polymer is preferably 260 to 600° C. In this case, the interface roughness of the TFE polymer layer 1 caused by decomposition gas (bubbles) of the AR polymer or by-product gas (bubbles) accompanying the reaction of the AR polymer itself can be effectively suppressed, and the adhesion of the TFE polymer layer 1 to the PI layer 1 is likely to be further improved.

[0044] The AR polymer may be either thermoplastic or thermosetting. If the AR polymer is thermoplastic, its plasticity improves the dispersibility of the AR polymer in the TFE polymer layer 1, and it is easy to form a dense and uniform TFE polymer layer 1. As a result, the adhesion of the TFE polymer layer 1 to the PI layer 1 and the physical properties (UV absorbency, etc.) of the multilayer film are easily improved. The thermoplastic AR polymer is preferably a thermoplastic polyimide, by which is meant a polyimide where the imidization is complete and no further imidization reaction takes place. The Tg of the thermoplastic AR polymer is preferably 200 to 500°C.

[0045] If the AR polymer is thermosetting, in other words, a cured product of a thermosetting aromatic polymer, the linear expansion property of the TFE polymer layer 1 is further reduced, and the occurrence of warping of the multilayer film is easily suppressed. The thermosetting AR polymer is preferably a thermosetting aromatic bismaleimide resin.Specific examples of the AR polymer include aromatic polyamideimides such as the "HPC" series (manufactured by Hitachi Chemical Co., Ltd.), and aromatic polyimides such as the "Neoprim" series (manufactured by Mitsubishi Gas Chemical Co., Ltd.), the "Spixeria" series (manufactured by Somar Co., Ltd.), the "Q-PILON" series (manufactured by PI Technical Research Institute Co., Ltd.), the "WINGO" series (manufactured by Wingo Technology Co., Ltd.), the "Tomide" series (manufactured by T&K Toka Co., Ltd.), the "KPI-MX" series (manufactured by Kawamura Sangyo Co., Ltd.), and the "Upia-AT" series (manufactured by Ube Industries, Ltd.).

[0046] When the liquid composition contains an AR polymer, the Tg of the AR polymer is equal to or lower than the melting temperature of the TFE polymer, and it is preferable that the melting temperature of the TFE polymer is 280 to 325°C and the Tg of the AR polymer is 180 to 320°C. In this case, not only are the TFE-based polymer and the AR-based polymer uniformly dispersed in the TFE-based polymer layer 1, which tends to improve the physical properties of the multilayer film, but also, in a high-temperature environment, the TFE-based polymer and the AR-based polymer highly interact with each other, which tends to further improve the heat resistance of the film.

[0047] The liquid composition preferably further contains a surfactant from the viewpoint of promoting the dispersion of the powder and the interaction with the AR polymer, and improving the physical properties of the formed TFE polymer layer 1. The surfactant is a component (compound) different from both the TFE polymer and the AR polymer. The surfactant is preferably nonionic. The hydrophilic portion of the surfactant is preferably a molecular chain containing a nonionic functional group (an alcoholic hydroxyl group, an oxyalkylene group, etc.). The hydrophobic portion of the surfactant is preferably a molecular chain containing an alkyl group, an acetylene group, a siloxane group, or a fluorine-containing group, and more preferably a molecular chain containing a siloxane group. In other words, the surfactant is preferably an acetylene-based surfactant, a silicone-based surfactant, or a fluorine-based surfactant, and more preferably a silicone-based surfactant.

[0048] A preferred embodiment of the surfactant is a copolymer of a (meth)acrylate having a perfluoroalkyl group or a perfluoroalkenyl group and a (meth)acrylate having an oxyalkylene group or an alcoholic hydroxyl group. Specific examples of such surfactants include the "Ftergent" series (manufactured by Neos), the "Surflon" series (manufactured by AGC Seimi Chemical Co., Ltd.), the "Megafac" series (manufactured by DIC Corporation), the "Unidyne" series (manufactured by Daikin Industries, Ltd.), "BYK-347", "BYK-349", "BYK-378", "BYK-3450", "BYK-3451", "BYK-3455", "BYK-3456" (manufactured by BYK Japan KK), "KF-6011", and "KF-6043" (manufactured by Shin-Etsu Chemical Co., Ltd.).

[0049] The liquid composition may further contain other materials within the range not impairing the effects of the present invention, such as a thixotropic agent, an antifoaming agent, an inorganic filler, a reactive alkoxysilane, a dehydrating agent, a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a brightening agent, a colorant, a conductive agent, a release agent, a surface treatment agent, a viscosity adjusting agent, and a flame retardant. These other materials may or may not be soluble in the liquid composition.

[0050] To dispose the liquid composition on the PI layer 1, the liquid composition may be applied to the surface of the PI layer 1. Examples of methods for applying the liquid composition include spraying, roll coating, spin coating, gravure coating, microgravure coating, gravure offset, knife coating, kiss coating, bar coating, die coating, fountain-meyer bar, and slot die coating.

[0051] After the liquid composition is placed on the PI layer 1, it is heated at a temperature higher than the melting point of the TFE-based polymer and lower than Tg+40° C. of PI 1 to form a layer 1 containing a TFE-based polymer. When heating the PI layer 1, it is preferable to hold it in a lower temperature range in advance to form a dry film. Specifically, when the liquid composition contains a liquid dispersion medium, it is preferable to hold it in a lower temperature range in advance to evaporate off the liquid dispersion medium (i.e., dry) to form a dry film. The temperature of the low temperature range is preferably 80 to 200° C. The temperature of the low temperature range means the temperature of the atmosphere during drying. The retention in the low temperature region may be carried out in one stage, or in two or more stages at different temperatures.

[0052] After obtaining the dry coating by the above procedure, it is preferable to further heat the dry coating at a temperature higher than the melting point of the TFE-based polymer and lower than Tg+40°C of PI1 (preferably lower than Tg+30°C of PI1) to bake the TFE-based polymer and form a TFE-based polymer layer 1 on the surface of the PI layer 1. The temperature is preferably maintained for 30 seconds to 5 minutes, more preferably 1 to 2 minutes. The atmosphere may be either normal pressure or reduced pressure. The atmosphere may be any of an oxidizing gas (oxygen gas, etc.), a reducing gas (hydrogen gas, etc.), and an inert gas (rare gas, nitrogen gas).

[0053] In the multilayer film obtained by the present method 1, the PI layer 1 and the TFE-based polymer layer 1 are preferably in direct contact with each other. That is, it is preferable that the TFE-based polymer layer 1 is directly formed (laminated) on the surface of the PI layer 1 without performing surface treatment with a silane coupling agent, adhesive, or the like. In this case, the physical properties of the multilayer film are unlikely to deteriorate. Note that, in the multilayer film obtained by the present method 1, due to the above-mentioned configuration, high adhesion is exhibited between the PI layer 1 and the TFE-based polymer layer 1 even if the PI layer 1 and the TFE-based polymer layer 1 are in direct contact with each other.

[0054] The thickness (total thickness) of the multilayer film obtained by Method 1 is preferably 25 μm or more, more preferably 50 μm or more, and is preferably 1000 μm or less. From the viewpoint of water resistance and electrical properties of the obtained film, the ratio of the thickness of the TFE-based polymer layer 1 to the thickness of the PI layer 1 is preferably 0.4 or more, more preferably 1 or more. The upper limit is preferably 5 or less. According to the present method 1, the adhesion between the layers is increased due to the above-mentioned action mechanism, so that a multilayer film having a high ratio and a thick TFE-based polymer layer 1 can be easily obtained. The thickness of the PI layer 1 is preferably 100 μm or less, more preferably 75 μm or less. The lower limit is preferably 10 μm or more. The thickness of the TFE-based polymer layer 1 is preferably 100 μm or less, more preferably 75 μm or less. The lower limit is preferably 10 μm or more.

[0055] When the TFE-based polymer layers 1 are formed on both sides of the PI layer 1, the ratio of the total thickness of the two TFE-based polymer layers 1 to the thickness of the PI layer 1 is preferably 1 or more. The above ratio is preferably 3 or less. In this case, the physical properties (high yield strength, low plastic deformation, etc.) of the PI 1 in the PI layer 1 and the TFE-based polymer (electrical properties such as low dielectric constant and low dielectric tangent, low water absorption, etc.) in the TFE-based polymer layer 1 are easily exhibited in a well-balanced manner. Furthermore, even in a multilayer film in which the above ratio is large and the TFE-based polymer layer 1 is thick, the occurrence of warping and peeling is easily suppressed.

[0056] The first multilayer film of the present invention (hereinafter also referred to as "present film 1") has a PI layer (PI layer 1) containing a PI (PI1) having a Tg, and layers (TFE-based polymer layer 1) containing a TFE-based polymer on both sides of the PI layer 1, and the Tg of PI1 is higher than the melting point of the TFE-based polymer and is not higher than the melting point of the TFE-based polymer + 60°C. The ranges of the TFE-based polymer and PI1 in Film 1 are the same as those in Method 1, including the preferred ranges.

[0057] The glass transition point of PI1 in the present film 1 is preferably the melting point of the TFE-based polymer +10° C. or more. The glass transition point of PI1 is preferably the melting point of the TFE-based polymer +50° C. or less, more preferably +40° C. or less. In this case, the peel strength between the layers and the water resistance are more likely to be increased. The TFE-based polymer layer 1 in the present film 1 preferably further contains an aromatic polymer. Examples of the aromatic polymer include the same aromatic polymers as those in the present method 1. The peel strength of the present film 1 is preferably 10 N / cm or more, more preferably 15 N / cm or more, and even more preferably 20 N / cm or more. In this case, the present film 1 can be suitably used as a printed circuit board material or a covering material for metal conductors (covering material for electric wires, etc.). The upper limit of the peel strength of the present film 1 is 100 N / cm.

[0058] This film 1 exhibits low water absorption (high water barrier properties) This is believed to be because the TFE-based polymer layer 1 and the PI layer 1 are not integrated together in a compatible manner, but exist independently of each other, and therefore the low water absorption of the TFE-based polymer complements the high water absorption of the PI 1. The water absorption rate of the present film 1 is preferably 0.3% or less, and more preferably 0.1% or less. In this case, the present film 1 is more resistant to water vapor permeation and exhibits excellent insulation properties for a long period of time, and is therefore particularly suitable for use as a coating material for metal conductors. The lower limit of the water absorption rate of the present film 1 is 0%.

[0059] The present film 1 is preferably produced by the present method 1. The preferred ranges of the thickness, etc. of the present film 1 are the same as those of the multilayer film obtained by the present method 1. The present film 1 preferably has a TFE-based polymer layer 1 on both sides of a PI layer 1 from the viewpoint of use in high-end electronic parts (printed circuit board materials, wire coating materials, etc.). The present film 1 can be easily and firmly bonded to other substrates due to the excellent adhesiveness of the surface of the TFE-based polymer layer 1. Examples of other substrates include metal foils and metal conductors.

[0060] The present film 1 may be made into a metal clad laminate by attaching metal foil to both sides of the TFE-based polymer layer 1. Such a metal clad laminate can be easily processed into a printed circuit board by processing the metal foil. Examples of metals that may be used to form the metal foil include copper, copper alloys, stainless steel, nickel, nickel alloys (including alloy 42), aluminum, aluminum alloys, titanium, and titanium alloys. The metal foil is preferably a copper foil, more preferably a rolled copper foil with no front and back or an electrolytic copper foil with front and back, and even more preferably a rolled copper foil. The rolled copper foil has a small surface roughness, so that even when the metal clad laminate is processed into a printed wiring board, the transmission loss can be reduced. In addition, the rolled copper foil is preferably used after immersing in a hydrocarbon organic solvent to remove the rolling oil.

[0061] The ten-point average roughness of the surface of the metal foil is preferably 0.01 to 4 μm. In this case, the adhesion to the TFE-based polymer layer 1 is improved, and a printed circuit board with excellent transmission characteristics is easily obtained. The surface of the metal foil may be roughened by a method such as forming a roughened layer, dry etching, or wet etching. The thickness of the metal foil may be any thickness that allows the metal clad laminate to exhibit sufficient function in its intended use, and is preferably less than 20 μm, more preferably 2 to 15 μm. The surface of the metal foil may be partially or entirely treated with a silane coupling agent.

[0062] When preparing the metal clad laminate, a method of laminating a metal foil on the surface of the TFE-based polymer layer 1 includes a method of hot pressing the present film 1 and the metal foil. The pressing temperature in the heat press is preferably 310 to 400°C. The heat pressing is preferably carried out at a vacuum of 20 kPa or less in order to prevent the inclusion of air bubbles and to prevent deterioration due to oxidation. In addition, it is preferable to heat the heat press after the above-mentioned degree of vacuum is reached. If the temperature is raised before the above-mentioned degree of vacuum is reached, the TFE-based polymer layer 1 is pressed in a softened state, i.e., in a state in which it has a certain degree of fluidity and adhesion, which may cause bubbles. The pressure in the heat press is preferably 0.2 to 10 MPa from the viewpoint of firmly adhering the TFE polymer layer 1 and the metal foil while suppressing damage to the metal foil.

[0063] The metal clad laminate obtained by the above procedure can be used as a flexible copper clad laminate or a rigid copper clad laminate for the manufacture of printed circuit boards. The printed circuit board can be manufactured, for example, by processing the metal foil in a metal clad laminate into a conductor circuit (pattern circuit) of a predetermined pattern by etching or the like, or by processing the metal clad laminate into a pattern circuit by electrolytic plating (semi-additive process (SAP process), modified semi-additive process (MSAP process), etc.). In the manufacture of a printed circuit board, after forming a pattern circuit, an interlayer insulating film may be formed on the pattern circuit, and a conductor circuit may be further formed on the interlayer insulating film. The interlayer insulating film may be formed from the liquid composition. In the manufacture of a printed circuit board, a solder resist may be laminated on a pattern circuit. The solder resist may be formed from the liquid composition. In the manufacture of printed circuit boards, a coverlay film may be laminated onto the pattern circuit.

[0064] A coated metal conductor can be obtained by coating a metal conductor with the present film 1. Such a coated metal conductor can be suitably used, for example, in electric wires and electric wire coils for aerospace applications. The material constituting the metal conductor is preferably copper, a copper alloy, aluminum, or an aluminum alloy, since these metals have excellent electrical conductivity. The cross-sectional shape of the metal conductor may be circular or rectangular. A metal conductor is disposed on one surface of the present film 1 and then covered with the present film 1, thereby producing a coated metal conductor. As a method for manufacturing such a coated metal conductor, the present film 1 may be cut into narrow strips to produce a tape, which is then spirally wound around the metal conductor. Alternatively, after the tape is wound around the metal conductor, another tape may be wound around the tape. The tape may also be wound around the metal conductor using a wrapping machine or the like.

[0065] The second manufacturing method of the present invention (hereinafter also referred to as “Method 2”) is a method for manufacturing a multilayer film having a PI layer 2 and a TFE-based polymer layer 2 formed on the surface of the PI layer 2, by placing a liquid composition containing a TFE-based polymer powder and a thermally decomposable polymer on the surface of a polyimide film layer (hereinafter also referred to as “PI layer 2”) and heating the liquid composition to form a layer containing a TFE-based polymer (hereinafter also referred to as “TFE-based polymer layer 2”).

[0066] The reason why a multilayer film with improved adhesion can be obtained by Method 2 is not entirely clear, but is thought to be as follows. When a liquid composition containing a powder is applied to the surface of the PI layer 2 and heated to form the TFE-based polymer layer 2, the polyimide contained in the PI layer 2 is denatured to a certain extent due to the thermal history, and the PI layer 2 inevitably deforms (shrinks). The present inventors considered that this deformation of the PI layer 2 reduces the adhesion between the two layers.

[0067] In this method 2, a liquid composition containing a thermally decomposable polymer in addition to the powder is placed on the surface of the PI layer 2, and heated to form a TFE-based polymer layer 2. The thermally decomposable polymer promotes the dispersion of the powder in the liquid composition and improves its uniform dispersion. Therefore, when the liquid composition is placed on the surface of the PI layer 2 and heated, the powder is densely packed, and the powder is melted and sintered to form a highly uniform TFE-based polymer layer 2, which improves the adhesion with the PI layer 2.

[0068] On the other hand, as the liquid dispersion medium is removed by heating, the affinity between the thermally decomposable polymer and the TFE-based polymer relatively decreases, and the thermally decomposable polymer becomes more likely to be repelled by the TFE-based polymer. Therefore, as the TFE-based polymer layer 2 is formed, the thermally decomposable polymer becomes more likely to segregate at the interface between the TFE-based polymer layer 2 and the PI layer 2. It is considered that the thermally decomposable polymer segregated at the interface acts as a plastic component, soft component, or adhesive component to mitigate the deformation of the PI layer 2 and improve the adhesion between the two layers. Method 2 will now be described further.

[0069] In the present method 2, the imide group density of the PI of the PI layer 2 is preferably 0.35 or less, more preferably 0.3 or less. If the imide group density of the PI is 0.35 or less, the heat shrinkage during heating is small, the warping of the produced multilayer film is small, and the dimensional stability is high. The imide group density of the PI is preferably 0.1 or more. In this case, the deformation of the PI layer 2 during heating and the melting of the powder proceed in a balanced manner, and the TFE-based polymer layer 2 and the PI layer 2 tend to have excellent adhesion.

[0070] The PI of the PI layer 2 preferably contains a unit based on an aromatic diamine having a structure in which two or more arylene groups are linked via a linking group. As the aromatic diamine, the same aromatic diamine as in Method 1 can be used. Furthermore, the PI of the PI layer 2 preferably contains a unit based on an aliphatic diamine. Examples of the aliphatic diamine include 1,2-ethylenediamine, 1,3-propylenediamine, 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 2-methyl-1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, and 1,12-dodecanediamine. The diamines may be used alone or in combination of two or more.

[0071] The PI of the PI layer 2 preferably contains units based on an acid dianhydride of an aromatic tetracarboxylic acid, and the acid dianhydride of the aromatic tetracarboxylic acid has a structure in which two phthalic anhydride structures are linked via a linking group. The PI of the PI layer 2 preferably has a Tg. The preferred embodiment of the PI in the present method 2 is the same as that of the PI 1 in the present method 1. In this case, it is easy to obtain a multilayer film that has excellent adhesion between adjacent layers and excellent drilling processability, and has no or very few wrinkles. The definition and scope of the TFE-based polymer in Method 2 are as described above.

[0072] In Method 2, the thermally decomposable polymer is thermally decomposed by heating, and therefore, as the TFE-based polymer layer 2 is formed, a thermal decomposition product derived from the thermally decomposable polymer segregates at the interface between the TFE-based polymer layer 2 and the PI layer 2. It is considered that the thermal decomposition product derived from the thermally decomposable polymer segregated at the interface acts as a plastic component, soft component, or adhesive component to further reduce deformation of the PI layer 2 and further improve the adhesion between the two layers. Therefore, in the multilayer film obtained by the present method 2, the TFE-based polymer layer 2 may contain a thermal decomposition product derived from a thermally decomposable polymer.

[0073] The thermally decomposable polymer is preferably a thermally decomposable (meth)acrylic polymer. The thermally decomposable (meth)acrylic polymer preferably has a fluoroalkyl group or a fluoroalkenyl group in the side chain. The number of carbon atoms in the fluoroalkyl group or fluoroalkenyl group is preferably from 4 to 16. In addition, an ether oxygen atom may be inserted between carbon atoms in the fluoroalkyl group or fluoroalkenyl group.

[0074] Specific examples of methacrylates constituting a (meth)acrylate-based polymer having a fluoroalkyl group or a fluoroalkenyl group in the side chain include CH2=C(CH3)C(O)OCH2CH2(CF2)4F, CH2=C(CH3)C(O)OCH2CH2(CF2)6F, CH2=CHC(O)OCH2CH2OCF(CF3)C(=C(CF3)2)(CF(CF3)2), CH2=C(CH3)C(O)OCH2CH2OCF(CF3)C(=C(CF3)2)(CF(CF3)2), CH2=CHC(O)OCH2CH2CH2CH2OCF(CF3)C(=C(CF3)2)(CF(CF3)2), CH2=C(CH3)C(O)OCH2CH2CH2CH2OCF(CF3)C(=C(CF3)2)(CF(CF3)2).

[0075] The thermally decomposable (meth)acrylic polymer preferably has a hydroxyl group or an oxyalkylene group in the side chain. The oxyalkylene group may be composed of one kind of oxyalkylene group or two or more kinds of oxyalkylene groups, in which case the different kinds of oxyalkylene groups may be arranged randomly or in a block form. The oxyalkylene group is preferably an oxyethylene group or an oxypropylene group, and particularly preferably an oxyethylene group.

[0076] Specific examples of methacrylates constituting a thermally decomposable (meth)acrylic polymer having a hydroxyl group or an oxyalkylene group in the side chain include CH2=C(CH3)C(O)OCH2CH2OH, CH2=C(CH3)C(O)OCH2CH2CH2CH2OH, CH2=C(CH3)C(O)(OCH2CH2)4OH, CH2=C(CH3)C(O)(OCH2CH2)9OH, CH2=C(CH3)C(O)(OCH2CH2) 23 OH, CH2=C(CH3)C(O)(OCH2CH2)9OCH3, CH2=C(CH3)C(O)(OCH2CH2) 23 OCH3, CH2=C(CH3)C(O)(OCH2CH2) 66OCH3, CH2=C(CH3)C(O)(OCH2CH2) 120 OCH3 is an example.

[0077] The thermally decomposable (meth)acrylic polymer preferably has a fluoroalkyl group or a fluoroalkenyl group and a hydroxyl group or an oxyalkylene group. Specific examples of such thermally decomposable (meth)acrylic polymers include copolymers of a (meth)acrylate having a fluoroalkyl group or a fluoroalkenyl group and a (meth)acrylate having a hydroxyl group or an oxyalkylene group.

[0078] An example of the pyrolysis product derived from a pyrolyzable (meth)acrylic polymer is a compound having a carboxyl group, a hydroxyl group, and a polyoxyalkylene group. The pyrolysis product is obtained, for example, when the pyrolyzable polymer is a (meth)acrylic polymer having a polyoxyalkylene group, preferably when the pyrolyzable polymer is a (meth)acrylic polymer having a hydroxyl group and a polyoxyalkylene group. The (meth)acrylic polymer is thermally decomposed, and the compounds having these hydrophilic groups are segregated at the interface, thereby improving the adhesion between the TFE-based polymer layer 2 and the PI layer 2. When the multilayer film obtained by the present method 2 is used as a printed circuit board material, a metal foil such as a copper foil is attached to the surface of the TFE-based polymer layer 2, and the compounds having these hydrophilic groups are segregated on the surface of the TFE-based polymer layer 2, thereby improving the adhesion to the metal foil.

[0079] The thermally decomposable (meth)acrylic polymer preferably has any one of the groups represented by the following formulae (1) to (5) in its side chain. In this case, the thermal decomposition property of the (meth)acrylic polymer is likely to be improved, and the decomposition products thereof, as plastic components, soft components, or adhesive components, are likely to further reduce the deformation occurring in the PI layer 2 and further improve the interlayer adhesion. Formula (1)-C(O)-OC(-R 11 )(-R 12 )(-R 13 ) Formula (2) -C(O)-OCH(-R21 )(-OR 22 ) Formula (3)-C(O)-OQ 3 -O-CF(CF3)(-R 31 ) Formula (4)-C(O)-OQ 4 -OC(CF3)(=C(-R 41 )(-R 42 )) Formula (5)-C(O)-OC(CF3)2(-R 51 ) The symbols in the formula have the following meanings.

[0080] R 11 , R 12 and R 13 is R 11 , R 12 and R 13 are each independently an alkyl group or an aryl group, or R 11 and R 12 is a hydrogen atom and R 13 is an aryl group or R 11 and R 12 are each independently a hydrogen atom or an alkyl group, and R 13 is an alkoxy group or R 11 is a hydrogen atom or an alkyl group, and R 12 and R 13 are groups which together form an alkylene group. R 21 and R 22 is R 21 is an alkyl group and R 22 is a fluoroalkyl group or is a group which together forms an alkylene group. Q 3 and Q 4 are each independently an alkylene group. R 31 is a perfluoroalkenyl group. R 41 and R 42 are each independently a perfluoroalkyl group. R 51 is an alkyl group or a cycloalkyl group.

[0081] Specific examples of polymers having a group represented by formula (1) include CH2=CX 11 C(O)OQ 5 -R 61 or CH2=CX 12 C(O)OC(-R 11 )(-R 12 )(-R 13 ) are mentioned. The symbols in the formula have the following meanings. X 11 represents a hydrogen atom, a chlorine atom or a methyl group. X 12 represents a hydrogen atom, a fluorine atom, a methyl group or a trifluoromethyl group. Q 5 represents an alkylene group or an oxyalkylene group. R 61 represents a perfluoroalkyl group or a perfluoroalkenyl group.

[0082] R 11 , R 12 and R 13 is as described above. X 11 and X 12 are preferably each independently a hydrogen atom or a methyl group. Q 5 and R 61 The carbon-containing groups each independently preferably have 1 to 16 carbon atoms. Q 5 is preferably -CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2O- or -CH2CH2CH2CH2O-. R 61 is preferably a perfluoroalkyl group having 1 to 6 carbon atoms or a perfluoroalkenyl group having 1 to 12 carbon atoms, and particularly preferably -(CF2)4F, -(CF2)6F or -OCF(CF3)C(=C(CF3)2)(CF(CF3)2).

[0083] Specific examples of monomers having a group represented by formula (1) include CH2=CHC(O)OCH2CH2(CF2)4F, CH2=CClC(O)OCH2CH2(CF2)4F, CH2=C(CH3)C(O)OCH2CH2(CF2)4F, CH2=CHC(O)OCH2CH2(CF2)6F, CH2=CClC(O)OCH2CH2(CF2)6F, CH2=C(CH3)C(O)OCH2CH2(CF2)6F, CH2=CHC(O)OCH 2CH2OCF(CF3)C(=C(CF3)2)(CF(CF3)2), CH2=C(CH3)C(O)OCH2CH2OCF(CF3)C(=C(CF3)2)(CF(CF3)2), CH2=CHC(O)OCH2C Examples include H2CH2CH2OCF(CF3)C(=C(CF3)2)(CF(CF3)2), CH2=C(CH3)C(O)OCH2CH2CH2CH2OCF(CF3)C(=C(CF3)2)(CF(CF3)2).

[0084] Specific examples of the monomer represented by formula (1) include the following monomers. Such monomers may be used alone or in combination of two or more. [ka]

[0085] The content of units based on such a monomer relative to all units contained in the (meth)acrylic polymer having a group represented by formula (1) is preferably 20 to 80 mol %. The fluorine content of the thermally decomposable polymer having a group represented by formula (1) is preferably from 10 to 45 mass %, particularly preferably from 15 to 40 mass %. The thermally decomposable polymer having a group represented by formula (1) is preferably nonionic. The mass average molecular weight of the thermally decomposable polymer having a group represented by formula (1) is preferably from 2,000 to 80,000, particularly preferably from 6,000 to 20,000. Specific examples of the group represented by formula (2) include the group represented by the formula -C(O)-O-CH(CH3)(-OR 22 ) is an example of a group represented by the formula: R 22is a fluoroalkyl group, preferably a fluoroalkyl group having 1 to 6 carbon atoms to which a fluorine atom is directly bonded, more preferably a fluoroalkyl group having 4 to 6 carbon atoms, and particularly preferably a fluoroalkyl group having 6 carbon atoms.

[0086] Specific examples of the group represented by formula (3) include the group represented by the formula -C(O)-OQ 6 -O-CF(CF3)(-C(=C(CF3)2)(CF(CF3)2)). Q 6 is -(CH2)2- or -(CH2)4-. Specific examples of the group represented by formula (4) include groups represented by the following formula (10). Formula (10)-C(O)-OQ 7 -OC(CF3)(=C(-CF(CF3)2)2) Q 7 is an alkylene group having 2 or 4 carbon atoms.

[0087] The liquid composition in Method 2 is a dispersion in which a TFE-based polymer powder is dispersed. The liquid composition preferably contains a liquid dispersion medium. The definition and scope of the liquid dispersion medium in Method 2 are the same as those of the liquid dispersion medium in Method 1, including preferred embodiments thereof. The content of the TFE polymer in the liquid composition is preferably 10% by mass or more, more preferably 25% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less. The content of the thermally decomposable polymer in the liquid composition is preferably 0.1% by mass or more, more preferably 1% by mass or more, and is preferably 20% by mass or less, more preferably 5% by mass or less.

[0088] The liquid composition may contain components other than the powder, the thermally decomposable polymer, and the liquid dispersion medium, as necessary. The liquid composition may contain polyimide, a polyimide precursor, or a bismaleimide, and preferably contains polyimide or a polyimide precursor. The polyimide precursor is a compound that forms a polyimide upon heating in forming the TFE-based polymer layer 2, and examples of such a compound include polyamic acid. Hereinafter, when the term polyimide is used, the term polyimide precursor is also included.

[0089] When the liquid composition contains polyimide or bismaleimide, the occurrence of warping and peeling in the formed TFE-based polymer layer 2 is sufficiently suppressed, and the adhesion to other substrates is also improved. In this case, the polyimide or bismaleimide contained in the TFE-based polymer layer 2 is highly dispersed, and the linear expansion property of the TFE-based polymer layer 2 is likely to be reduced. The polyimide or bismaleimide is preferably an aromatic polyimide or an aromatic bismaleimide. In this case, the polyimide or bismaleimide present on the surface layer of the TFE-based polymer layer 2 interacts with the PI layer 2. Specifically, it is considered that the aromatic ring of the polyimide or bismaleimide and the aromatic ring of the PI present near the interface between the TFE-based polymer layer 2 and the PI layer 2 are stacked, thereby improving the adhesion of the TFE-based polymer layer 2 to the PI layer 2. Furthermore, when the TFE-based polymer layer 2 contains an aromatic polyimide or an aromatic maleimide, the multilayer film obtained by the present method 2 tends to have excellent peel strength and UV absorbency (that is, UV processability).

[0090] The polyimide may be a thermoplastic or a thermosetting material. If the polyimide is thermoplastic, the polyimide exhibits plasticity when heated, which improves the dispersibility of the polyimide in the TFE-based polymer layer 2 and makes it easier to form a dense and uniform TFE-based polymer layer 2. As a result, the adhesion of the TFE-based polymer layer 2 to the PI layer 2 is easily improved. By thermoplastic polyimide is meant a polyimide in which the imidization has been completed and no further imidization reaction takes place.

[0091] If the polyimide is thermosetting, in other words, if it is a cured product of a thermosetting polyimide, the linear expansion property of the TFE polymer layer 2 is further reduced, and it is easy to suppress the occurrence of warping in the multilayer film. As the thermosetting polyimide, a polyimide having no plasticity, which is formed by the imidization reaction of a polyimide precursor (such as polyamic acid), is preferable.

[0092] Specific examples of polyimides include the "Neoprim" series (manufactured by Mitsubishi Gas Chemical Company, Inc.), the "Spicceria" series (manufactured by Somar), the "Q-PILON" series (manufactured by PI Technical Research Institute, Inc.), the "WINGO" series (manufactured by Wingo Technology Co., Ltd.), the "Tomide" series (manufactured by T&K Toka Corporation), the "KPI-MX" series (manufactured by Kawamura Sangyo Co., Ltd.), and the "Upia-AT" series (manufactured by Ube Industries, Ltd.).

[0093] The polyimide is preferably a polymer that is soluble in the liquid dispersion medium of the liquid composition. This enhances the interaction between the polyimide and other components (TFE-based polymer, liquid dispersion medium) in the liquid composition, and the dispersibility of the liquid composition is likely to be improved. As a result, during heating in forming the TFE-based polymer layer 2, the fluidity of the polyimide is increased and the polyimide is highly dispersed. Therefore, the physical properties based on the TFE-based polymer, such as electrical properties, are highly expressed, and the TFE-based polymer layer 2 having higher adhesion to the PI layer 2 is likely to be formed.

[0094] The solubility of the polyimide in the liquid dispersion medium of the liquid composition at 25° C. (g / 100 g of solvent) is preferably 5-30. The bismaleimide is preferably a thermosetting aromatic bismaleimide resin, in which case the linear expansion of the TFE polymer layer 2 is further reduced, making it easier to suppress warping of the film.

[0095] The liquid composition in Method 2 may further contain other materials within the scope of not impairing the effects of the present invention. Examples of such other materials include the same materials as those in Method 1. To dispose the liquid composition on the PI layer 2, the liquid composition may be applied to the surface of the PI layer 2. Examples of a method for applying the liquid composition include the same method as the method for applying the liquid composition in Method 1.

[0096] In the present method 2, when the PI layer 2 is heated after the liquid composition is placed, it is preferable to hold the temperature in the low temperature range to form a dry coating. Specifically, when the liquid composition contains a liquid dispersion medium, it is preferable to hold the liquid composition in a lower temperature range in advance to evaporate off the liquid dispersion medium (i.e., dry) to form a dry coating. The temperature of the low temperature range is preferably 80 to 200°C. The temperature of the low temperature range means the temperature of the atmosphere during drying. The retention at a temperature in the low temperature region may be carried out in one stage, or in two or more stages at different temperatures.

[0097] After obtaining the dry coating by the above procedure, it is preferable to further heat the dry coating in a temperature range (hereinafter also referred to as "baking range") that exceeds the holding temperature in the low temperature range, and bake the TFE-based polymer to form a TFE-based polymer layer 2 on the surface of the PI layer 2. The temperature of the baking range means the temperature of the atmosphere during baking.

[0098] It is believed that the formation of the TFE-based polymer layer 2 proceeds as the powder particles are densely packed and the TFE-based polymer fuses together. When the liquid composition contains a thermoplastic polyimide, a TFE-based polymer layer 2 made of a mixture of a TFE-based polymer and a polyimide is formed, and when the liquid composition contains a thermosetting polyimide or a thermosetting maleimide, a TFE-based polymer layer 2 made of a TFE-based polymer and a cured product of a polyimide or a thermosetting maleimide is formed.

[0099] The firing atmosphere may be either normal pressure or reduced pressure, and may be any of an oxidizing gas (oxygen gas, etc.), a reducing gas (hydrogen gas, etc.), and an inert gas (rare gas, nitrogen gas). The temperature in the baking zone is preferably equal to or higher than the melting temperature of the TFE-based polymer, and particularly preferably from 300 to 380°C. The time for maintaining the temperature of the baking zone is preferably from 30 seconds to 5 minutes, and particularly preferably from 1 to 2 minutes.

[0100] When the PI in the PI layer 2 has a Tg, it is preferable to place a liquid composition on the surface of the PI layer 2 and heat it at a temperature higher than the melting point of the TFE-based polymer and lower than or equal to Tg+40° C. of the PI to form the TFE-based polymer layer 2. In this case, a preferred embodiment of the method for forming the TFE-based polymer layer 2 in Method 2 is the same as that of the method for forming the TFE-based polymer layer 1 in Method 1.

[0101] In the multilayer film obtained by the present method 2, the PI layer 2 and the TFE-based polymer layer 2 are preferably in direct contact with each other. The preferred ranges of the thickness of the multilayer film and the thickness of each layer obtained by Method 2 are similar to those of the multilayer film and the thickness of each layer obtained by Method 1.

[0102] The second multilayer film of the present invention (hereinafter also referred to as “present film 2”) has a PI layer 2 and, on both sides of the PI layer 2, TFE-based polymer layers 2 containing a heat-meltable TFE-based polymer and a thermally decomposable polymer. The ranges of the TFE-based polymer and PI in Film 2 are the same as those in Method 2, including the preferred ranges.

[0103] The TFE-based polymer layer 2 in the present film 2 preferably contains an aromatic polymer. In this case, the present film 2 is likely to have excellent processability. As the aromatic polymer, the same aromatic polymer as in the present method 1 can be used. The TFE-based polymer layer 2 in the present film 2 preferably contains a pyrolysis product derived from a pyrolyzable polymer. In this case, the adhesion between adjacent layers in the present film 2 is likely to be improved, and the present film 2 is likely to have excellent water resistance.

[0104] The peel strength of the present film 2 is preferably 10 N / cm or more, more preferably 15 N / cm or more, and even more preferably 20 N / cm or more. In this case, the present film 2 can be suitably used as a printed circuit board material or a covering material for metal conductors (covering material for electric wires, etc.). The upper limit of the peel strength of the present film 2 is 100 N / cm.

[0105] This film 2 exhibits low water absorption (high water barrier properties). This is thought to be because the polymer layer 2 and the PI layer 2 are not integrated together in a compatible manner, but exist independently of each other, and therefore the low water absorption of the TFE-based polymer complements the high water absorption of the PI. The water absorption rate of the present film 2 is preferably 0.1% or less, more preferably 0.07% or less, and even more preferably 0.05% or less. In this case, the present film 2 is more resistant to water vapor permeation and exhibits excellent insulation properties for a long period of time, and is therefore particularly suitable for use as a coating material for metal conductors. The lower limit of the water absorption rate of the present film 2 is 0%.

[0106] A preferred embodiment of the configuration of the present film 2 is the same as a preferred embodiment of the configuration of the multilayer film of the present method 2. The multilayer film of the present method 2 can be easily and firmly bonded to other substrates due to the excellent adhesiveness of the surface of the TFE-based polymer layer 2. Examples of the other substrates include metal foils and metal conductors. The multilayer film of the present method 2 may be made into a metal clad laminate by attaching a metal foil to both sides of the TFE-based polymer layer 2. Such a metal clad laminate can be easily processed into a printed circuit board by processing the metal foil. EXAMPLES

[0107] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. [Example 1] <<Materials used>> <PIフィルム> PI film 11: FS-100 (product name, manufactured by SKC Kolon PI), thickness 25 μm, Tg = 315 ° C, tensile modulus = 8.0 GPa PI Film 12: UPILEX (product name, manufactured by Ube Industries, Ltd.), thickness 25 μm, Tg = 350 °C, tensile modulus = 9.1 GPa PI Film 13: FG-100 (product name, manufactured by PI Advanced Materials), thickness 25 μm, Tg = 330 °C, tensile modulus = 10.0 GPa

[0108] <TFE-based polymer> TFE-based polymer 11: A polymer containing 98.0 mol%, 1.9 mol%, and 0.1 mol% of TFE units, PPVE units, and NAH units, respectively, in this order (melting temperature: 300 °C) TFE-based polymer 12: A polymer containing 98.5 mol% and 1.5 mol% of TFE units and PPVE units, respectively, in this order (melting temperature: 305 °C) Note that TFE-based polymer 11 has 1000 carbonyl group-containing groups per 1 × 10 6 carbon atoms in the main chain, and TFE-based polymer 12 has 40 such groups. <Powder of TFE-based polymer> Powder 11: Powder of TFE-based polymer 11 (average particle size (D50): 1.9 μm) Powder 12: Powder of TFE-based polymer 12 (average particle size (D50): 1.5 μm)

[0109] <AR-based polymer> Thermoplastic aromatic polyimide 11: A block copolymer of 3,3',4,4'-benzophenone tetracarboxylic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride with 2,4-diaminotoluene and 2,2-bis{4-(4-aminophenoxy)phenyl}propane <Polymer dispersant> (Meth)acrylic polymer 11: A copolymer of (meth)acrylate having a perfluoroalkenyl group and (meth)acrylate having a polyoxyethylene monoglycol group

[0110] <Liquid composition> A liquid composition 11 containing 40 mass % of powder 11 and 4 mass % of (meth)acrylic polymer 11 was prepared using N-methyl-2-pyrrolidone (NMP) as a liquid dispersion medium. A varnish of the thermoplastic aromatic polyimide 11 (solvent: NMP) was added to the liquid composition 11 to prepare a liquid composition 12 further containing 0.5 mass % of the thermoplastic aromatic polyimide 11.

[0111] <<Production Example>> <Multilayer film> [Example 1-1] The liquid composition 12 was applied to one side of the PI film 11 by a small diameter gravure reverse method, and passed through a ventilation drying oven (oven temperature: 150°C) for 3 minutes to remove the NMP and form a dry film. The liquid composition 12 was similarly applied to the other side and dried to form a dry film. Next, the PI film 11 with the dry coating formed on both sides was passed through a far-infrared oven (oven temperature: 320°C) for 5 minutes to melt and bake the powder 11. As a result, a TFE-based polymer layer (thickness: 25 µm) containing the TFE-based polymer 11 and a thermoplastic aromatic polyimide was formed on both sides of the PI film 11, and a multilayer film 1 in which the TFE-based polymer layer, the PI film 11, and the TFE-based polymer layer were directly formed in this order was obtained.

[0112] [Example 1-2] A multilayer film 12 was obtained in the same manner as in Example 1-1, except that Powder 11 was changed to Powder 12. [Example 1-3] A multilayer film 13 was obtained in the same manner as in Example 1-1, except that the PI film 11 was changed to the PI film 12. [Example 1-4] A multilayer film 14 was obtained in the same manner as in Example 1-1, except that the liquid composition 12 was changed to the liquid composition 11.

[0113] [Example 1-5] A multilayer film 15 was obtained in the same manner as in Example 1-1, except that the melting and sintering temperature was changed to 300°C. [Example 1-6] A multilayer film 16 was obtained in the same manner as in Example 1-1, except that the melting and sintering temperature was changed to 350°C. [Example 1-7] A multilayer film 17 was obtained in the same manner as in Example 1-1, except that the melting and sintering temperature was changed to 360°C.

[0114] [Example 1-8] Films (thickness: 50 μm) obtained by melt extrusion molding the TFE-based polymer 11 were placed on both sides of the PI film 11, and vacuum pressed at 320° C. for 15 minutes to obtain a multilayer film 18 in which a TFE-based polymer layer, a PI film 11, and a TFE-based polymer layer were directly formed in this order. [Example 1-9] A multilayer film 19 was obtained in the same manner as in Example 1-1, except that the PI film 11 was changed to the PI film 13.

[0115] <<Evaluation items>> <Appearance> The obtained multilayer film was placed on a smooth glass surface, and the presence or absence of warping (waviness) was confirmed and evaluated according to the following criteria. ◯: No warping was observed. △: Warping was observed. ×: Not only was warping observed, but wrinkles were also observed. Multilayer film 19 was free of wrinkles and had the highest surface smoothness among the multilayer films.

[0116] <Heat shrinkage rate> The resulting multilayer film was cut into a 12 cm square sample, and the heat shrinkage rate was determined by the following method. At 25°C, a straight line of about 10 cm in length was drawn on the sample, and the distance between the endpoints of the line was taken as the initial length L0. The sample was then heat-treated at 320°C for 5 minutes and cooled to 25°C, after which the linear distance L1 between the endpoints of the line drawn on the sample was measured, and the thermal shrinkage rate (%) was calculated using the following formula 1 and evaluated according to the following criteria. Heat shrinkage rate (%) = (1-L1 / L0) x 100 Formula 1 〇: Heat shrinkage rate ≦2% △: 2%<Heat shrinkage rate<3% ×: Heat shrinkage rate ≧3%

[0117] <Adhesion> A rectangular test piece having a length of 100 mm and a width of 10 mm was cut out from the obtained multilayer film. The PI film and the TFE-based polymer layer were then peeled off from the test piece from one end in the length direction to a position 50 mm from the end. Next, the test piece was peeled off at 90 degrees at a tensile speed of 50 mm / min using a tensile tester (manufactured by Orientec Co., Ltd.) with the position 50 mm from one end in the length direction as the center, and the maximum load was taken as the peel strength (N / cm) and evaluated according to the following criteria. ○: Peel strength ≧10N / cm △: 5N / cm< peel strength<10N / cm ×: Peel strength ≦ 5N / cm

[0118] <Workability> Copper foil (electrolytic copper foil CF-T49A-DS-HD2-12, Fukuda Metal Foil & Powder Co., Ltd.) was placed on both sides of the obtained multilayer film and pressed under vacuum at 340° C. for 20 minutes to produce a double-sided copper-clad laminate. Using a laser processing machine, a UV-YAG laser with a wavelength of 355 nm was irradiated on each double-sided copper-clad laminate so as to circle around a circumference with a diameter of 100 μm. This resulted in the formation of circular through-holes in the double-sided copper-clad laminate. The laser output was 1.2 W, the laser focal diameter was 25 μm, the number of circles around the circumference was 20, and the oscillation frequency was 40 kHz.

[0119] Then, a piece of the double-sided copper-clad laminate containing the through-hole was cut out and solidified with a thermosetting epoxy resin. Then, the piece was polished until the cross section of the through-hole was exposed, and the cross section of the part where the through-hole was formed was observed under a microscope, and the periphery of the through-hole was visually confirmed and evaluated according to the following criteria. ◯: No scraping or peeling was observed at the layer interface inside the through hole. Δ: Scraping was observed at the layer interface inside the through hole, but no peeling was observed. ×: Chipping and peeling were observed at the layer interface inside the through hole.

[0120] <Water resistance> The water absorption rate was measured in accordance with the method of JIS K7209:2000A. The obtained multilayer film was cut out into a 10 cm square to prepare a test piece. Next, this test piece was dried at 50 °C for 24 hours and cooled in a desiccator. The mass of the test piece at this point was taken as the mass of the test piece before water immersion. Thereafter, this dried test piece was immersed in pure water at 23 °C for 24 hours. Then, the test piece was taken out of the pure water, and after quickly wiping off the surface moisture, the mass was measured within 1 minute and taken as the mass of the test piece after water immersion.

[0121] The mass change rate of the test piece before and after immersion was determined as the "water absorption rate" of the multilayer film, and the water resistance was evaluated according to the following criteria. 〇: The water absorption rate is 0.3% or less. △: The water absorption rate exceeds 0.3% and is less than 1%. ×: The water absorption rate is 1% or more. The respective evaluation results are collectively shown in Table 1.

[0122]

Table 1

[0123] [Example 2] <<Materials Used>> <TFE-based polymer> TFE-based polymer 21: A polymer having polar functional groups, containing 98.0 mol%, 1.9 mol%, and 0.1 mol% of TFE units, PPVE units, and NAH units in this order (melting temperature 300 °C) Note that TFE-based polymer 21 has 1000 carbonyl group-containing groups per 1 × 10 6 carbon atoms in the main chain. <Powder of TFE-based polymer> Powder 21: Powder of TFE-based polymer 21 (average particle size (D50): 2 μm)

[0124] <(Meth)acrylic-based polymer> (Meth)acrylic-based polymer 21: Copolymer of CH2=C(CH3)COO(CH2)4OCF(CF3)C(=C(CF3)2)(CF(CF3)2) and CH2=C(CH3)COO(CH2)4(OCH2CH2)9OH (Meth)acrylic polymer 22: CH2=C(CH3)COO(CH2)2(CF2)6F and CH2=C(CH3)COO(CH2)4(OCH2CH2) 23 Copolymer of OH <Liquid dispersion medium> NMP: N-methyl-2-pyrrolidone

[0125] <<PIフィルム> > PI film 21: A film (thickness: 50 μm) of polyimide (imide group density: ≦0.35) in which the acid anhydride monomer is BPDA (3,3',4,4'-biphenyltetracarboxylic dianhydride) and the diamine monomer is BAFL (9,9-bis(4-aminophenyl)fluorene). The PI film 21 has a Tg of 320° C. and a tensile modulus of elasticity of 9.5 GPa. PI film 22: A film (thickness: 50 μm) of polyimide (imide group density: >0.35) in which the acid anhydride monomer is BPDA and the diamine monomer is PDA (p-phenylenediamine). The PI film 22 has a Tg of 315° C. and a tensile modulus of elasticity of 8.2 GPa.

[0126] <<Liquid composition>> Liquid composition 21: Powder dispersion containing powder 21 (30% by mass), thermoplastic polyimide (1% by mass), (meth)acrylic polymer 21 (3% by mass) and NMP (balance). Liquid composition 22: Powder dispersion containing powder 21 (30% by mass), thermoplastic polyimide (1% by mass), (meth)acrylic polymer 22 (3% by mass) and NMP (balance). Liquid composition 23: Powder dispersion containing powder 21 (30% by mass), (meth)acrylic polymer 21 (3% by mass), and NMP (balance). Liquid composition 24: Powder dispersion containing Powder 21 (30% by mass) and NMP (balance)

[0127] <<Production Example>> <Multilayer film> [Example 2-1] Manufacturing example of multilayer film 21 The liquid composition 21 was applied to one surface of the PI film 21 by a small diameter gravure reverse method, and dried in a ventilated drying oven (oven temperature: 150°C) for 3 minutes to remove the NMP and form a dry coating. The liquid composition 21 was similarly applied to the other surface and dried to form a dry coating. Next, the powder 21 was melted and baked by passing it through a far-infrared furnace (furnace temperature: 320° C.) for 20 minutes. As a result, a polymer layer (thickness: 25 μm) containing the TFE-based polymer 21 and a thermoplastic polyimide was formed on the outermost surfaces of both sides of the PI film 21, and a multilayer film 21 having a TFE-based polymer layer, a PI film layer, and a TFE-based polymer layer in this order was obtained.

[0128] [Example 2-2] Example of manufacturing multilayer film 22 A multilayer film 22 was obtained in the same manner as in Example 2-1, except that the PI film 21 was changed to the PI film 22. [Example 2-3] Manufacturing example of multilayer film 23 A multilayer film 23 was obtained in the same manner as in Example 2-1, except that the liquid composition 21 was changed to the liquid composition 23. [Example 2-4] Example of manufacturing multilayer film 24 A multilayer film 24 was obtained in the same manner as in Example 2-1, except that the liquid composition 21 was changed to the liquid composition 22. [Example 2-5] Manufacturing example of multilayer film 25 A multilayer film 25 was obtained in the same manner as in Example 2-1, except that the liquid composition 21 was changed to the liquid composition 24.

[0129] <<Evaluation items>> <Decomposition products on the layer surface> The surface of the TFE-based polymer layer is analyzed by total reflection-infrared absorption spectroscopy (ATR-IR analysis) and AFM-IR, and evaluated based on the type of functional group detected. If a carboxyl group is detected by the former method, and if an etheric oxygen atom is detected by the latter method, it is judged as "present" as decomposition products, and if neither is detected, it is judged as "absent" as decomposition products.

[0130] <Adhesion> The adhesion of each of the multilayer films 21 to 25 was evaluated in the same manner as in Example 1. The results showed that the order of adhesion was highest for multilayer film 21, followed by multilayer film 22, multilayer film 23, and multilayer film 24, with the adhesion of multilayer film 25 being lower than those of these multilayer films.

[0131] <Water resistance> The water resistance was evaluated in the same manner as in Example 1. <Appearance> The appearance was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0132] [Table 2] [Industrial Applicability]

[0133] According to the present invention, a multilayer film having excellent adhesion and drilling processability and having no or very few wrinkles can be obtained. Also, according to the present invention, a multilayer film having excellent adhesion between layers can be obtained. The multilayer film of the present invention can be processed and used for antenna parts, printed circuit boards, aircraft parts, automobile parts, etc. Furthermore, a metal conductor covered with such a multilayer film exhibits high insulation properties for a long period of time and can be suitably used for electric wires or conductive coils for aerospace use.

Claims

1. A method for producing a multilayer film, comprising the steps of: placing a liquid composition containing a powder of a heat-fusible tetrafluoroethylene-based polymer and a heat-decomposable polymer on a surface of a polyimide film layer; heating the liquid composition to form a layer containing the tetrafluoroethylene-based polymer; and obtaining a multilayer film having the polyimide film layer and layers containing the heat-fusible tetrafluoroethylene-based polymer and the heat-decomposable polymer or a heat decomposition product derived from the heat-decomposable polymer on both sides of the polyimide film layer, The method for producing a multilayer film, wherein the thermally decomposable polymer is a thermally decomposable (meth)acrylic polymer having a fluoroalkyl group or a fluoroalkenyl group on the side chain and a hydroxyl group or an oxyalkylene group on the side chain.

2. A multilayer film comprising a polyimide film layer and layers on both sides of the polyimide film layer, the layers including a heat-fusible tetrafluoroethylene polymer and a heat-decomposable polymer or a heat decomposition product derived from the heat-decomposable polymer, The multilayer film, wherein the thermally decomposable polymer is a thermally decomposable (meth)acrylic polymer having a fluoroalkyl group or a fluoroalkenyl group on the side chain and a hydroxyl group or an oxyalkylene group on the side chain.

3. 2. The method for producing a multi-layer film according to claim 1, wherein the polyimide of the polyimide film layer has an imide group density of 0.35 or less.

4. The thermally meltable tetrafluoroethylene polymer has a main chain carbon number of 1×10 6 The method for producing a multilayer film according to claim 1 or 3, wherein each of the carbonyl-containing groups has 10 to 500 carbonyl-containing groups.

5. 3. The multilayer film according to claim 2, wherein the polyimide of the polyimide film layer has an imide group density of 0.35 or less.

6. The thermally meltable tetrafluoroethylene polymer has a main chain carbon number of 1×10 6 The multilayer film according to claim 2 or 5, wherein each of the multilayer films has 10 to 500 carbonyl-containing groups.

Citation Information

Patent Citations

  • Fluorine-based resin laminate improved in surface property and its production

    JP1997157418A

  • Laminate of polyimide and fluoroplastic, production thereof and insulating tape for coating electric wire using the laminate

    JP2000211081A

  • Dielectric substrate containing polyimide core layer and high-temperature fluoropolymer bonding layer, and method related thereto

    JP2005035300A

  • Semiconductor device, its manufacturing method, and adhesive sheet for manufacturing same

    JP2005142401A

  • Inkjet ink

    JP2011162581A